Assessing the contribution of land and water management approaches to sustainable land management and achieving land degradation neutrality - Hartmann, Lisa; Walz, Yvonne; Hansohm, Jonas; Domingos Vellozo, Leticia; Walinder, Elizabeth; Andreeva, Olga; Harari, Nicole; Hendrickson, John; Kinyua, Ivy; Parrotta, John; Rath, Daniel; Sylvén, Magnus; et al. (Frontiers in Sustainable Resource Management, 2024)
The framework of land degradation neutrality (LDN) and the concept of sustainable land management (SLM) are ways to instigate action required to address land degradation. Although land and water management approaches supporting SLM and the achievement of LDN exist, the transition to sustainable agricultural systems is hindered by various factors and the achievement of LDN is lagging behind. More information on such approaches is needed to sensitize decision-makers for fostering their implementation. This study responds to this need by examining the alignment of the following land and water management approaches with SLM and LDN: agroecology, climate-smart agriculture, conservation agriculture, forest landscape restoration, integrated agriculture, regenerative agriculture, and rewilding. The alignment assessment used a formative methodological approach combining literature review and extensive expert consultations, and is structured along the SLM and LDN pillars of ecosystem health, food security, and human-wellbeing, each comprised by several criteria, as well as selected cross-cutting socioeconomic criteria that span all pillars. The results indicate that each of the approaches contributes to SLM and the achievement of LDN in different ways and to varying degrees, with none of the approaches embracing principles or practices that directly conflict with the criteria of SLM and LDN. A higher degree of alignment was identified for the ecosystem health and food security pillars, while most gaps in alignment concern criteria of the human wellbeing pillar along with certain cross-cutting criteria. The results of the assessment led to the identification of entry points for addressing gaps in alignment via supplementary activities that directly target the gaps during project planning and implementation, as well as through adhering to principles and established guidelines. Importantly, conclusions about the degree of alignment or about gaps in alignment of an approach with SLM and LDN criteria are conceptually indicative, but may change in actual practice depending on where and how projects are implemented. Notwithstanding, clarifying the approaches' contribution to SLM and the achievement of LDN can help overcome the lack of formal intergovernmental recognition of the approaches, prevent misinterpretation, and ensure their strategic inclusion in broader efforts to remedy land degradation.